A Comparative Study of Boredom and Hopelessness in Najib Mahfouz's The Beggar and Abbas Maroufi's Symphony of the Dead: بررسی تطبیقی ملال و ناامیدی در رمان گدا اثر نجیب محفوظ و سمفونی مردگان عباس معروفی (Journal of the College of Languages (JCL), 2025)
Despair and the lack of a positive and hopeful outlook, along with the destruction of one’s purposeful efforts, are themes that lead to poor mental health. In positive psychology, it is believed that concepts such as despair can lead to various illnesses. This study aims to examine despair in Naguib Mahfouz’s The Beggar and Abbas Maroufi's Symphony of the Dead using an analytical-descriptive approach to examine its impact on the characters’ behaviour, as well as to reveal the prevailing atmosphere in the two novels. The results indicate that the despair and boredom dominating the novels are primarily due to the sick and depressed character of Omar. Economic conditions do not play a significant role in this context, although oppressive conditions are not without influence. In the novel Symphony of the Dead, boredom and despair are symbolic and significant as two fundamental and prominent feelings in the world the author depicts. These feelings often arise due to the pessimistic conditions and the unsatisfactory endings described for the characters and society. The conflict between tradition and modernity in family and society, as well as the outbreak of World War II, are among the reasons for this despair, which manifests in themes such as the description of sorrow, atmospheres filled with despair, boredom in marital and familial relationships, regret, weakness, and incapability.چکیدهپژوهش حاضر درصدد است به روش تحلیلی -توصیفی ضمن بررسی ناامیدی در رمان گدا اثر نجیب محفوظ و سمفونی مردگان عباس معروفی به بازیابی آن در رفتار شخصیّت‌های داستان‌های مذکور، بپردازد. نتایج به دست آمده بیانگر آن است که ناامیدی و ملال حاکم  و شرایط اقتصادی در این زمینه نقشی نداشته‎اند. هرچند شرایط خفقان‌زده در این میان بی‌تأثیر نبوده است. در رمان "سمفونی مردگان"، ملال و ناامیدی به عنوان دو احساس اساسی و بارز در جهانی که نویسنده آن را به تصویر می‌کشد، نمادین و مهم هستند. این دو احساس اغلب به دلیل شرایط بدبینانه و پایان غیرمطلوبی که برای شخصیّت‌ها و جامعه توصیف می‌شود، به وجود می‌آیند. تقابل سنت و مدرنیته در خانواده و اجتماع و نیز وقایع جنگ جهانی دوم از دلایل این ناامیدی هستند که در مضامینی چون وصف غم و اندوه، فضای یأس‌آلود، ملال در روابط زناشویی و خانوادگی، حسرت، ضعف و ناتوانی پدیدار می‌شود.